2019
DOI: 10.3390/su11072138
|View full text |Cite
|
Sign up to set email alerts
|

Overtourism: Between the Right to Travel and Residents’ Rights

Abstract: Debates on overtourism, as a challenging phenomenon, are becoming more and more active. The purpose of this integrative review paper is to discuss the right to travel and residents’ rights in the context of overtourism and sustainable tourism, analyzing different scientific and legal sources. The integrative review analysis shows that overtourism and sustainable tourism are important contexts influencing the changing meaning of the right to travel and the right to live. On the one hand, the overtourism context… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
81
0
10

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(92 citation statements)
references
References 41 publications
(77 reference statements)
1
81
0
10
Order By: Relevance
“…These are superficially associated with tourismphobia, especially by the media and some politicians. Recently, new contributions regarding the different aspects of overtourism have emerged [63][64][65][66][67][68], underlining the impacts on residents' communities and the aggravation of the consequences of uncontrolled tourism growth in urban and cultural destinations.…”
Section: Discussionmentioning
confidence: 99%
“…These are superficially associated with tourismphobia, especially by the media and some politicians. Recently, new contributions regarding the different aspects of overtourism have emerged [63][64][65][66][67][68], underlining the impacts on residents' communities and the aggravation of the consequences of uncontrolled tourism growth in urban and cultural destinations.…”
Section: Discussionmentioning
confidence: 99%
“…It should be emphasized that stakeholders have different levels of awareness about the economic benefits of sustainability. This is confirmed by the results of research that showed that the perceptions of the sustainability of the stakeholders involved in rural tourism development were very different [20]. Moreover, tourism enterprises often lack awareness of how efforts and investment in sustainable business operations can also significantly boost competitiveness and profitability, while increasing customer and host community satisfaction [3].…”
Section: Introductionmentioning
confidence: 89%
“…It becomes necessary to conduct research in the field of sustainability in tourism, which is emphasized in the literature [20]. In particular, research on tourists' awareness of their impact on sustainable development appears to be important.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Briefl y, the issue that overtourism as a concept describes is the excessive negative impact of tourism on host communities and / or the natural environment (Koens et al, 2018). In their theoretical work, authors Perkumiene and Pranskuniene (2019) polemically examine the concepts of overtourism and sustainable tourism. Th ey conclude that the overtourism context places greater emphasis on hearing the voices of residents, while on the other hand the sustainable tourism context entails discussions of the right to travel, according greater importance to tourist voices.…”
Section: Theoretical Backgroundmentioning
confidence: 99%